THE STUDY OF COMITY AND RESPONSIBLE STUDENT INTO BROKEN HOME BACKGROUND FAMILY ON SOCIAL INTERACTION IN THE SCHOOL - Dartim Nan Sati, Gina Nurtya Lestari Iim Siti Masyitoh (Jurnal Civicus, 2014)
In the opinion of Willis (2009, page 66) from a broken home will be born children who experienced a personality crisis, so any custom behavior. They are susceptible to interference. The case of a broken home is often found in schools with poor adjustment, such as lazy learning, aggressive, ditching, and love against the teacher. Therefore to minimize misconduct and develop custom character comity and responsibility among students despite the family conflict (broken home) Students should be given particular character education comity character and responsibility. The approach used in this study is a qualitative approach to the case study method. Data collected through observation, interviews, library research and study documentation. Subjects in this documentation are: Coordinator of Guidance and Counselling teachers, civic education teachers, homeroom, students broken home who were randomly selected, As well as the parents of a broken home. The study found that: 1. Student broken home has character and responsibility comity. The first education given within the family With regard to the education of character, making every student to know and understand the importance of having and practicing an attitude of respect and character of such responsibilities. 2. Factors that can shape and influence the development of the character and attitude of respect is the responsibility of environmental factors and education. Be a family first and foremost in providing direction, guidance and education on which the child lives.3. Student broken home have not been able to practice the two main characters properly. As well, they were able to practice the comity character, but have not been able to practice Character responsible attitude, and vice versa. 4. Efforts are made of the school in terms of fostering an attitude of respect and character of the student's responsibility broken home in a social interaction In school is to conduct coaching and guidance on a regular basis. In addition, the school collaborates with the parents. The school and parents must come together in terms of educating, guiding, nurture, observe, supervise, as well as cultivate an attitude of respect character and responsibility.Keywords : Comity, Responsible, Family, Broken Home, Social Interaction